Application of Data Mining to Measure the Level of Satisfaction with Public Facilities and Services at STMIK Kaputama Binjai Using Linear Regression Method - Rendy Zuhriansyah Pratama; Sihombing, Marto; Ambarita, Indah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This study aims to analyze the level of satisfaction of STMIK Kaputama Binjai students with physical facilities (classrooms, laboratories, prayer rooms, wifi) and general services (administration, academic guidance, library, security, campus cleanliness) using multiple linear regression methods. Data were collected through questionnaires from students in the 2022/2023 academic year. The results showed that both variables have a significant effect on student satisfaction, with a regression coefficient of physical facilities of 0.40 and general services of 0.59, indicating that general services have a greater impact. Prediction of student satisfaction reached an accuracy level of 98% with a Mean Absolute Percentage Error (MAPE) value of 2%. Laboratory facilities and internet access (wifi) are the dominant factors affecting satisfaction. Based on these findings, improvements in both aspects are recommended to increase student satisfaction and institutional competitiveness.